4th World University Woodball Championship 2014 - Universiti Malaysia Perlis (Universiti Malaysia Perlis, 2014)
4th World University Woodball Championship 2014 organized by Universiti Malaysia Perlis (UniMAP), 21st - 26th October 2014 at Universiti Malaysia Perlis.